Do We Still Need Reference Services in the Age of Google and Wikipedia?. Issue 4 (1st October 2016) - Buss, Stephen P.
ABSTRACT: With the continuing development of web resources and Internet search utilities, the role of reference services is changing in the modern library. Traditional ready reference is in decline, but the need for broad-based research support will continue for the foreseeable future. As librarians adapt to the evolving research environment, libraries are experimenting with alternative models of reference services. Far-reaching calls to adopt one model or abandon another, such as the traditional reference desk, are off target given that each library must adapt to its own local situation and determine how best to serve its constituents.